2022
DOI: 10.1029/2021jb023824
|View full text |Cite
|
Sign up to set email alerts
|

Constraining Upper Mantle Viscosity Using Temperature and Water Content Inferred From Seismic and Magnetotelluric Data

Abstract: Mantle viscosity controls the pace of upper mantle dynamics, including rates for plate motions, subduction deformation, small-scale convection, and glacial isostatic adjustment (GIA) processes. In particular, upper mantle viscosity influences the rate of surface uplift and associated sea level change caused by GIA, which is the viscous response of the Earth to changes in ice mass. However, surface uplift rates measured by geodesy (e.g., GNSS) in places with modern-day ice sheets such as in Greenland and Antarc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 97 publications
(188 reference statements)
0
3
0
Order By: Relevance
“…However, grounding line positions, and thus stability, of these glaciers are affected by solid earth uplift due to ice thinning. West Antarctica is characterized by low upper mantle viscosities (although absolute mantle viscosity is still poorly constrained and could benefit from an inversion using a variety of geophysical data (Ramirez et al., 2022)), and large ice mass loss (The IMBIE Team, 2018); a combination that may help to stabilize the ice sheet.…”
Section: Discussionmentioning
confidence: 99%
“…However, grounding line positions, and thus stability, of these glaciers are affected by solid earth uplift due to ice thinning. West Antarctica is characterized by low upper mantle viscosities (although absolute mantle viscosity is still poorly constrained and could benefit from an inversion using a variety of geophysical data (Ramirez et al., 2022)), and large ice mass loss (The IMBIE Team, 2018); a combination that may help to stabilize the ice sheet.…”
Section: Discussionmentioning
confidence: 99%
“…If the Lehmann is due to an abrupt change in the volume of either melting or dehydration, it could also be associated with an abrupt vertical change in the electrical resistivity. Resistivity anomalies resolved in magnetotelluric studies of the uppermost mantle, however, are primarily marked by a sharp increase near 100–150 km rather than 220–240 km (Moorkamp, 2022; Ramirez et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Since water content in olivine is one of the major controls on mantle rheology (e.g., Hirth & Kohlstedf, 2003), higher water contents in the cratonic mantle should, all else being equal, make it weaker than the Eastern Branch lithospheric mantle. Selway (2015) suggested that small grain sizes in the Eastern Branch lithosphere, which may still remain as a scar from Pan‐African deformation, could contribute to weakening the Eastern Branch lithosphere and could outweigh the impact of water content (e.g., Ramirez et al., 2022). Mantle xenoliths from the volcanoes along the rift zone (Pello Hill and Elodoi) do indeed dominantly have porphyroclastic textures with smaller olivine grain sizes (0.4–2 mm Baptiste et al., 2015).…”
Section: Electrical Structure Metasomatism and Volcanism In Northern ...mentioning
confidence: 99%